Nucleic acids and protein changes in granulosa cells of developing goat follicles - SANGHA, G K; MARWAHA, ANURADHA (The Indian Journal of Animal Sciences, 2014)
Quantitative changes revealed increased amounts of DNA, RNA and protein contents in the granulosa cells from small (5mm) follicles through medium (2-5mm) follicles. The increase being much more (i.e. up to 3-fold) for RNA in large follicles. All 3 estimates increased with size of the follicle. The values (ng/granulosa cells) were 0.021±0.002, 0.034±0.002, 0.042±0.009 fat DNA. 0.025±0.03, 0.041±0.005. 0.075±0.008 for RNA, 0.210±0.02, 0.330±0.032, 0.500±0.026 for proteins in granulosa cells of small, medium and large sized follicles respectively. These biochemical variations in macromolecules have been discussed in relation to the role of granulosa cells in growing follicles.